The Role of STEM-Based Project-Based Learning in Developing Future Competencies: A Systematic Review - Rulli Hari Utomo; Sudiyanto Sudiyanto; Supianto Supianto (Universitas Sebelas Maret, 2025)
The STEM project-based learning technique (STEM-PjBL) is acknowledged as an effective educational instrument for cultivating 21st-century competencies, including critical thinking, creativity, and problem-solving. This study seeks to evaluate the efficacy, obstacles, and potential of executing STEM-PjBL by a systematic literature evaluation of publications from 2019 to 2023 in the Scopus database. The evaluation identified 14 papers that fulfilled the inclusion requirements, analyzed via a qualitative descriptive technique, concentrating on learning outcomes, innovative solutions, and implementation issues. The findings indicate that STEM-PjBL consistently improves students' skills across different educational levels, with the integration of methodologies like Ethno-STEM and STEAM enriching the learning experience. Nonetheless, challenges like as constrained resources, teacher preparedness, and the lack of a standardized framework persist as significant impediments. This study promotes ongoing teacher training, equitable allocation of resources, and supporting educational policies to enhance the efficacy of STEM-PjBL. This technique can establish a basis for educational reforms that meet the requirements of the 21st century by mitigating these constraints.